Optimizing the Change Decision Mechanism in Administrative Reconsideration: Key to Effectively Resolving Administrative Disputes - Hongyan Yu (Studies in Law and Justice, 2025)
How to resolve administrative disputes quickly and effectively is the key to realizing the goal orientation of the main channel of administrative reconsideration. As a kind of decision for the substantive settlement of administrative disputes, the new Administrative Reconsideration Law has refined and emphasized the importance of the decision to change. Looking at the current situation of China’s change decision system, there are still imprecise scope of application, the order of application is unclear, subjective exclusion of review organs and other dilemmas. In order to solve the above problems, the change decision should be positioned as the core of the administrative reconsideration decision system, focusing on the realization of the function of administrative reconsideration to substantively resolve administrative disputes, following the legitimacy, clarifying the scope of administrative reconsideration, constructing a typology of administrative reconsideration, expanding the exceptions to prohibit unfavorable administrative reconsideration, and speeding up the construction of an administrative reconsideration talent team by perfecting the means of the public administrative reconsideration system. Optimize the administrative environment for reconsideration and related systems by speeding up the establishment of reconsideration teams and improving the system for publicizing reconsideration decisions, in order to ensure that the decision to amend can be applied properly and efficiently.